Development and evaluation of the manufacture of a coronary stent for the South African market - Lehmann, Markus (Division of Biomedical Engineering, 2017)
The need for economic treatment of coronary heart disease in South Africa and the popularity of coronary stent implantation as an effective treatment increases. Stent implants have had to be imported to date with significant cost involved. The project in hand therefore deals with the evaluation of the possibilities of economical local manufacture of a coronary stent. The design of several coronary stents currently in use was carefully analysed and the results of clinical application described in the literature were reviewed. After evaluating the patent situation, a suitable design concept was chosen, based primarily on the availability of manufacturing equipment. The design concept of choice is the balloon expandable slotted tube variety. Stents of this most popular slotted tube design are usually laser cut out of a tube with good results. Since there was no suitable laser cutting equipment in use in South Africa, it was undertaken to manufacture stent prototypes by spark erosion to establish the general suitability of the method for stent manufacturing. The initial design was adjusted several times to the manufacturing process and suitable machine parameters were evaluated. For comparison a stent of a similar design was laser cut by an established European manufacturer. The geometry of the most favourable prototypes was analysed by computer simulation using finite element analysis, followed by simple physical tests of deployment and radial strength. The quality of manufacturing was evaluated with electron microscopy. The computational and mechanical test results of the design analysis yielded largely satisfactory results, but it was found that the manufacturing process of spark erosion is not suitable to manufacture products that would have to compete on the current sophisticated market. With the spark erosion equipment, neither a satisfying surface quality nor acceptable geometrical tolerances could be achieved. This was particularly obvious after comparison with the laser cut stent sample of the same design. An improvement in quality of the spark erosion process would require extensive fine-tuning and would increase the already very long manufacturing time and the cost significantly. Subcontracted laser cutting in Europe was found to be more reliable and economical.